PLANKTON AND HYDROLOGICAL FACTORS AT KANDLA IN THE GULF OF KUTCH DURING 1960—1963 - Dhawan, Rajinder M (Indian Journal of Fisheries, 2011)
The present studies relate mainly to the hydrological factors in the Gulf of Kutchat Kandlafrom August 1960 to December 1963. The seasonal variationin the temperature,salinity, pH, dissolved oxygen, inorganic phosphate, nitrite and silicate and theirinfluence on plankton have been discussed. Temperature seems to be the only factorfollowing the same pattern of variation during all the years. Dissolved phosphate andnitrite have a definite seasonal cycle among the nutrient salts. Fluctuation in salinityin the gulf appears to be erratic. Salinity and pH show a direct relationship in thisarea. The seasonal fluctuations of different plankters, both phytoplankton and zooplankton,have been discussed. The fluctuations in the phytoplankton count do not seemto be reflected on the total volume of plankton. It is seen that zooplankton content ismainly responsible for the variation in the plankton biomass